Breeding a New Apple Hybrid Population with the Vf Gene Through Marker-Assisted Selection - Georgeta Maria BIVOLARIU (GUZU); Ioan ZAGRAI; Claudiu MOLDOVAN; Smaranda Doina ROȘU MAREȘ; Anca Maria CHIOREAN; Luminița Antonela ZAGRAI; Mirela Irina CORDEA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture)
Apple scab, caused by Venturia inaequalis, is one of the most damaging pathogens affecting apple species. Cross combinations were made between the Salva cv. (female parent), a valuable local cultivar known for its fruit quality and used as a donor of the Vf resistance gene, and Jonathan (male parent), a variety widely cultivated but susceptible to scab. The Vf gene was first identified in Malus floribunda Clone 821, which was subsequently transferred to commercial varieties through various breeding programs. To confirm the presence of the Vf gene, the progeny from this cross was tested using Marker-Assisted Selection (MAS) with one dominant primer pair (AM19) and two codominant primers (AL07 and VFC) to distinguish between homozygous and heterozygous genotypes. From the crossing, 67 hybrids were obtained, of which 35.8% (24 hybrids) were classified as resistant (heterozygous - Vfvf), while 64.2% (43 hybrids) were classified as susceptible (recessive homozygotes - vfvf). This population of hybrids resistance to Venturia inaequalis represents a good starting point in obtaining cultivars with resistance to scab.